Motivierende Lernzugänge als Ausgangspunkt der Professionalisierung angehender Lehrer_innen - Caruso, Carina; Adammek, Christine; Bonanati, Sabrina; Wiescholek, Sybille (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Im Artikel werden drei verschiedene Lernzugänge (kom-petenzorientiertes, ästhetisches und biographisches Lernen) vorgestellt und aus theoretischer Perspektive deren motivierender Gehalt für selbstreguliertes Lernen in Praxisphasen des Lehramtsstudiumsherausgearbeitet. Als theoretische Grund-lage dient die Selbstbestimmungstheorie als zentrale motivationale Theorie zur Erklärung selbstbestimmten Handelns.
Keywords: ästhetische Forschung; Biographiearbeit; Praxissemester; Professionalisierung; selbstreguliertes Lernen; Motivation / aesthetic research; biographical work; long-term internship; profes-sionalization; self-regulated learning; motivation

Experiential or Self-Regulated Learning: A Critical Reflection of Entrepreneurial Learning Processes - Fust, Alexander Paul; Jenert, Tobias; Winkler, Christoph (Entrepreneurship Research Journal)
Research on entrepreneurial learning highlights the importance of experience and prior knowledge to entrepreneurial success. However, a conundrum remains and we are still seeking answers as to why some novice entrepreneurs learn successfully from their experiences and succeed, while some experienced entrepreneurs fail with their ventures. In order to advance the discussion about the role of experience during entrepreneurial learning, our critical reflection aims to (1) highlight some of the shortcomings of experiential learning theory (ELT) and (2) illustrate how alternative theoretical perspectives have the potential to advance our conceptual understanding of entrepreneurial learning processes. We argue for an explanation of entrepreneurial learning as a dynamic and self-regulated process that relies on planning, monitoring, and self-reflection.
Keywords: entrepreneurial learning; experiential learning; self-regulated learning